A Novel Approach for Efficient Conversion Tracking in Mobile Applications: Leveraging EventLinking and Beacon Events - Sambu Patach Arrojula (North American Journal of Engineering Research, 2022)
In the context of analytics, determining the source of a conversion, such as a user registration or product purchase, is a criticalyet challenging task. Applications typically have multiple entry points leading to these important actions, such as various adsor UI elements. Product owners seek to identify which entry points are most effective in driving conversions. Traditionally,applications track these entry points through complex event instrumentation that propagates data from screen to screen, resultingin high maintenance overhead and increased potential for errors. In this paper, we propose a novel design that simplifies eventinstrumentation while efficiently determining the source entry points for conversions. We demonstrate how this design can beimplemented on both the client side and the backend, ensuring robust conversion tracking through analytic events